2000
DOI: 10.1046/j.1523-5378.2000.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Curing Helicobacter pylori Infection in Patients with Duodenal Ulcer Does Not Provoke Gastroesophageal Reflux Disease

Abstract: Our data show that successful eradication of H. pylori infection does not increase the incidence of GERD in duodenal ulcer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 12 publications
0
55
1
8
Order By: Relevance
“…The association between H. pylori eradication and the development of newly and recurrent GERD is still controversial although various studies have been performed [18][19][20][21][22][23][24]. Moreover, there is still no evidence whether the presence of GERD before eradication therapy could affect the H. pylori eradication success rate.…”
Section: Discussionmentioning
confidence: 99%
“…The association between H. pylori eradication and the development of newly and recurrent GERD is still controversial although various studies have been performed [18][19][20][21][22][23][24]. Moreover, there is still no evidence whether the presence of GERD before eradication therapy could affect the H. pylori eradication success rate.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a higher rate of esophagitis in patients who had their H. pylori eradicated compared to the group in which the infection had continued. Following this first study, other trials were carried out, either confirming LABENZ' work (8,9,14) or reporting contradictory results (1,24,36,38,41,42,44) .…”
Section: Introductionmentioning
confidence: 88%
“…These phenomena are seen more often in non-flat scars than in flat scars defined by chromoendoscopy (7,8). Reduced prostaglandin concentration in the ulcer scar tissue and H. pylori infection (15) are the major abnormalities seen in non-flat scars (7,8).…”
Section: S6mentioning
confidence: 99%
“…Eradication therapy is successful in 80-90% (but not 100%) but has some adverse effects and is not applicable to H. pylori-negative ulcers. In addition, elimination of H. pylori may, in some patients, aggravate reflux esophagitis (14), although this issue remains controversial (15,16). Furthermore, elimination of H. pylori may increase the appetite by altering leptin (17) and result in an increase in body weight (18).…”
Section: S6mentioning
confidence: 99%